ANALYSIS OF PRODUCTION PERFORMANCE BASED ON GREEN SUPPLY CHAIN MANAGEMENT CRITERIA - Yudiansyah Yudiansyah; Tukhas Shilul Imaroh (Dinasti Publisher, 2020)
PT. XYZ is one of the companies engaged in the salt processing industry in Indonesia. The development of this industry, in addition to having a positive impact on the economy also has the potential for negative impacts on the environment if not managed properly. This condition is inseparable from the production process which produces many defects and rejects. One way to reduce these negative impacts is by measuring performance that is integrated with the environment (Green Supply Chain Management). The researcher uses the green SCOR model which refers to the SCOR (Supply Chain Operation Reference) model from the Supply Chain Council to identify green supply chain management performance indicators. Then use AHP (Analytical Hierarchy Process) to determine the level of importance of green supply chain management performance indicators. There are six categories of processes used in measuring the performance of green supply chain management, namely plan, source, make, deliver, return and waste management, but research is focused on the make process that focuses on the salt production process. The results of measurements indicate that the value of the performance of green supply chain management of PT. XYZ in 2017 amounted to 75.4 and 2018 amounted to 72.3 is still below 80 even though it is nearing the target but is still being controlled and efforts are made to improve. But when in 2019 it decreased to 46.6 which shows far below the target and needs to be done immediately. As for the 17 performance indicators measured, there are 9 performance indicators that need to be improved, namely reusable material, the number of machine troubles, the number of process rejects, recycleable rejects, the amount of waste, the amount of product defects, recycleable defects, production costs and waste handling costs.